If f(x) = x + 4 and g(x) = 2x - 3, find (g - f)(2). Write the answer as an integer.

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

If f(x) = x + 4 and g(x) = 2x - 3, find (g - f)(2). Write the answer as an integer.

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

by definition we can write: \[\left( {g - f} \right)\left( x \right) = g\left( x \right) - f\left( x \right) = \left( {2x - 3} \right) - \left( {x + 4} \right) = ...?\]
okay
hint: \[\begin{gathered} \left( {g - f} \right)\left( x \right) = g\left( x \right) - f\left( x \right) = \left( {2x - 3} \right) - \left( {x + 4} \right) = \hfill \\ \hfill \\ = 2x - 3 - x - 4 = ...? \hfill \\ \end{gathered} \]

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

I got 6
I got a different result
I got 9
hint: \[\begin{gathered} \left( {g - f} \right)\left( x \right) = g\left( x \right) - f\left( x \right) = \left( {2x - 3} \right) - \left( {x + 4} \right) = \hfill \\ \hfill \\ = 2x - 3 - x - 4 = x - 7 \hfill \\ \end{gathered} \]
now, replace x with 2, please what do you get?
-5
that's right!
so would the answer be -5
yes!
If f\left( x \right) = \frac{{2{x^2}}}{{x - 1}}, evaluate for f(-4). Write only the answer as a decimal or fraction. also got stuck on this question
is your function, like this: \[f\left( x \right) = \frac{{2{x^2}}}{{x - 1}}\]
yes
we have to replace x with -4, so we can write: \[f\left( { - 4} \right) = \frac{{2{{\left( { - 4} \right)}^2}}}{{ - 4 - 1}} = ...?\]
-13
hint: \[f\left( { - 4} \right) = \frac{{2{{\left( { - 4} \right)}^2}}}{{ - 4 - 1}} = \frac{{2 \times 16}}{{ - 5}} = ...?\]
27
are you sure? what is 2*16=...?
32
correct! so our answer is: \[f\left( { - 4} \right) = \frac{{2{{\left( { - 4} \right)}^2}}}{{ - 4 - 1}} = \frac{{2 \times 16}}{{ - 5}} = \frac{{32}}{{ - 5}} = - \frac{{32}}{5}\]
okay

Not the answer you are looking for?

Search for more explanations.

Ask your own question